2003
DOI: 10.1002/macp.200300019
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Properties of Sugar Sensitive Copolymer of N‐Isopropylacrylamide and 3‐(Acrylamido)phenylboronic Acid

Abstract: Summary: The copolymer of N‐isopropylacrylamide and 3‐(acrylamido)phenylboronic acid (82:18, $\overline M _{\rm n}$ = 47 000 g · mol−1) was prepared by free radical polymerization. The copolymer showed typical thermal precipitation behavior in aqueous solutions, its precipitation temperature (TP) being increased from 23 to 32 °C by increasing the pH from 6.5 to 9.7, because of ionization of the phenylboronate units. The pKa was evaluated as 8.9 ± 0.1 from the effect of pH on TP. At pH > 9, i.e., in the anionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 35 publications
0
94
2
Order By: Relevance
“…In addition, the sharp shifting of the LCST onset by the incorporation of the two co-monomers, implies the relatively random distribution of the co-monomers within the polymer backbone, reflecting homogenous conversion rates for all monomers; 79,80 this was demonstrated by monitoring the diminution of the 1 H NMR signal of the vinyl protons of APBA (5.7, 6.3 and 6.45 ppm) and NIPAAm (5.5, 6.08 and 6.2 ppm) during the polymerisation of a model poly(NIPAAm-co-APBA) copolymer, where it was confirmed that NIPAAm was only slightly more reactive than the APBA residues (10% more reactive in the first hour of the reaction, Fig. S1b †).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sharp shifting of the LCST onset by the incorporation of the two co-monomers, implies the relatively random distribution of the co-monomers within the polymer backbone, reflecting homogenous conversion rates for all monomers; 79,80 this was demonstrated by monitoring the diminution of the 1 H NMR signal of the vinyl protons of APBA (5.7, 6.3 and 6.45 ppm) and NIPAAm (5.5, 6.08 and 6.2 ppm) during the polymerisation of a model poly(NIPAAm-co-APBA) copolymer, where it was confirmed that NIPAAm was only slightly more reactive than the APBA residues (10% more reactive in the first hour of the reaction, Fig. S1b †).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers synthesized some bioengineering copolymers containing phenylboronic acid linkages by radical copolymerization and chemical modification methods, which are exhibit glugose-, RNA-and DNA-sensitive behavior [33][34][35][36]. Recently, we report the synthesis and chracterization of organoboron copolymers by complex-radical copolymerization of p-vinylphenylboronic acid with N-isopropylacrylamide (NIPA), maleic and citraconic anhydrides, maleimide and chemical modification of poly(NIPArand-MA)s with organoboron amine, as well as synthesis of supramacromolecular poly(ethylene imine) macrocomplexes and PEO long branched derivatives of organoboron copolymers having stimuli-responsive and high HeLa cell transfection behavior [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 20 mm sodium bicarbonate buffer (pH 9.0) a gradual decrease in the contact angle due to droplet spreading could be seen. This spreading can be explained in terms of ionization of the PBA groups of the copolymer at the above pH, [29] endowing the grafted surface with better wettability. The presence of 0.1 m fructose in the bicarbonate buffer resulted in even stronger changes in the contact angle and the droplet area with time, however (see Figure 1 and Figure 2), with the contact angle gradually decreasing down to 318-358 over about 550 s. The experiment was repeated three times on fresh surfaces: the results were somewhat scattered (indicated by the error bars in Figure 1), but the obtained contact 3-GPTMS-glass nonhydrolyzed 54 AE 4 epoxy groups hydrolyzed to diols [a] 40 AE 3 3-GPTMS-glass with immobilized 3-APBA [a] 45 AE 4 www.chemeurj.org angles were always smaller than those observed just in the presence of the buffer.…”
Section: Resultsmentioning
confidence: 98%